Soluxion Paint - Anuar, Nurlisa Arina; Khairuddin, Nursyazwana; Yushadi, Nur Nasywa Hanani; Fatkhuddin, Muhammad Faiz Dinie; Akashah, Nor Ariqah Alia; Ariffin, Nurul Azrin (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Soluxion Paint is a next-generation photovoltaic paint system designed to revolutionize the way industrial buildings harness solar energy. Soluxion Paint presents an innovative alternative to conventional solar panels by offering a lightweight, scalable, and easy-to-apply solution. This paint-based technology consists of a multi-layer structure including an internal insulation layer, a conductive base, a photovoltaic light-absorbing layer, and a weather-resistant transparent coating. As for the uniqueness of this innovative product, such a layer plays a crucial role in ensuring efficient energy conversion, temperature regulation, and long-term durability.The insulation component contributes to reducing heat gain, improving indoor comfort and lowering the energy demand for cooling systems such as air conditioners—especially crucial in warehouses storing temperature-sensitive goods. Additionally, the photovoltaic layer actively converts sunlight into electricity, supporting critical warehouse operations including conveyor belts, electric forklift charging stations, lighting systems, and automated machinery. Soluxion Paint not only simplifies the process of adopting renewable energy but also reduces maintenance costs and enhances aesthetic integration. The application process, using tools like airless spray systems, allows for uniform coverage on various surfaces without extensive modification to existing structures. In a market where sustainability, efficiency, and innovation are becoming essential, this product supports industries in achieving long-term energy goals and environmental compliance.